텍스타일 산업의 사회적가치 창출을 위한 디자인개발 사례연구 -환경친화적 개념 적용사례를 중심으로 - 박현주; Park Hyun Joo; 황지원; Hwang Ji Won (기초조형학연구, 2023)
유럽 텍스타일 산업은 친환경 지속가능성과 산업목표를 이루기 위한 유럽연합의 그린딜 정책과 함께 변화하고 있다. 이러한 사회적 배경 속에서 우리 텍스타일 산업 실정에 맞는 지속가능한 방법의 독창적 텍스타일 디자인연구가 필요하다. 이 연구의 목적은 텍스타일 제품에 응용할 수 있는 다양한 윤리적 제작과 건전한 소비의식의 확산에 있다. 그래서 연구방법은 텍스타일산업 현황을 통한 최근 방향성, 디자인 활용방안을 고찰하여 소재 개발의 다양성 및 적절성을 재고한다. 미래 텍스타일디자인의 폭넓은 적용범위로써 타 분야를 살피고, 건축외피에 주목한 아키텍스타일 개념을 조사한다. 이를 바탕으로 텍스타일 산업의 다양성을 위한 아트텍스타일 사례 분석과 선행사례연구와 윤리적 연구, 제작에 대한 가능성도 모색한다. 다양한 건축외피 이미지에 선행연구를 가상 적용하여 텍스타일디자인 산업의 융합적 활용 및 부가가치 향상 가능성도 함께 알아본다. 그 결과, 텍스타일 산업의 현황 분석을 통해 최근의 활용 동향은 의류패션 외 기타건축 분야의 텍스타일 활용이 증가추세임을 확인했다. 이로써 텍스타일디자인의 적용을 위한 다양한 분야와의 연계적 접근이 적절함을 알 수 있었다. 텍스타일·패션 산업체인 페라가모, 에르메스의 소비자와 사회를 위한 지속가능성 창출 사례를 통해 실현가능한 가치를 고찰했다. 텍스타일 산업에 있어서 사회적가치란 타 산업과 마찬가지로 환경을 지키는 방법의 생산뿐 아니라, 브랜드 철학을 전승하는 사회적 협력, 상생, 환경적 요소가 고려된 기업의 활동이 중요한 의미가 있다. 이러한 연구과정으로 환경친화적 개념의 아키텍스타일을 대입한 확장된 영역의 텍스타일디자인과 폐섬유의 역할을 연구하고, 선행사례 건축외피 이미지의 가상 적용을 통해 개발한 디자인의 활용 제안과 적용 가능성을 확인할 수 있다. The European textile industry is joining the Green Deal policy for the EU economy to achieve industrial goals and eco-friendly sustainability. In this social background, it is necessary to study original textile design in a sustainable method suitable for the situation of our textile industry. The purpose of this study is to create various ethical products that can be applied to textiles and to spread healthy consumption consciousness. Therefore, the research method reconsiders the diversity and appropriateness of material development by considering the recent direction and design utilization plan through the current status of the textile industry. As a wide range of applications of future textile designs, we examine other fields and investigate the concept of the architectural envelope. Based on this, it also seeks the possibility of analyzing the case of art textile for the diversity of the textile industry and researching precedent cases, ethical research and production. The possibility of convergent use of the textile design industry and improvements of added value by virtually applying previous studies to various architectural envelope images is also examined. As a result, through the analysis of the current status of the textile industry, it was confirmed that the use of textiles in other architectural fields other than clothing fashion is on the rise. As a result, it was found that a linkage approach with various fields for the application of textile design was appropriate. The feasible value was considered through examples of sustainability creation for consumers and society of Ferragamo and Hermes. A social value in the textile industry is like other industries, not only the production of ways to protect the environment, but also the activities of companies that take into account social cooperation and environmental factors that pass on brand philosophy. Through this research process, we can study the role of textile design and waste fiber in extended areas using Architextiles of eco-friendly concept, and confirm the applicability and the developed design through virtual application of architectural images in previous cases.